Effects of Electrode Drift in Transcranial Direct Current Stimulation - Adam J. Woods (Brain Stimulation, 2015)
Background: Conventional transcranial direct current stimulation (tDCS) methods involve application of weak electrical current through electrodes encased in saline-soaked sponges affixed to the head using elastic straps. In the absence of careful preparation, electrodes can drift from their original location over the course of a tDCS session. Objective: The current paper investigates the influence of electrode drift on distribution of electric fields generated by conventional tDCS. Methods: MRI-derived finite element models of electric fields produced by tDCS were used to investigate the influence of incremental drift in electrodes for two of the most common electrode montages used in the literature: M1/SO (motor to contralateral supraorbital) and F3/F4 (bilateral frontal). Based on these models, we extracted predicted current intensity from 20 representative structures in the brain. Results: Results from separate RM-ANOVAs for M1/SO and F3/F4 montages demonstrated that 5% incremental drift in electrode position significantly changed the distribution of current delivered by tDCS to the human brain (F's > 8.6, P's < 0.001). Pairwise comparisons demonstrated that as little as 5% drift was able to produce significant differences in current intensity in structures distributed across the brain (P's < 0.03). Conclusions: Drift in electrode position during a session of tDCS produces significant alteration in the intensity of stimulation delivered to the brain. Elimination of this source of variability will facilitate replication and interpretation of tDCS findings. Furthermore, measurement and statistically accounting for drift may prove important for better characterizing the effects of tDCS on the human brain and behavior.